1984
DOI: 10.1203/00006450-198404001-01054
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Fungal Colonization in Very Low Birth-Weight (Vlbw) Infants

Abstract: W e pre vio us l y documented fungal sep sis i n 4% of our VLBW « 1500g)infants, wit h a 79%mor t al i ty. To deter min e sources , t i min g and s it es of acquisi t ion i n t his high r i s k pop ul a t i on , week l y o ropha ryngeal, r e c t a l , g ro i n and , if int ubated , endot rac h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
0
16

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(132 citation statements)
references
References 0 publications
13
103
0
16
Order By: Relevance
“…[2][3][4] Early colonization of the skin and mucous membranes with Candida species can progress to candidemia in up to 60% of ELBW infants. [5][6][7] In addition to mortality, neonatal candidemia has been associated with increased NICU lengths of stay and hospital costs. 8 Kaufman et al 7 published the only prospective, randomized, double-blind clinical trial to date that demonstrates effectiveness and safety of fluconazole administration in preventing fungal colonization and invasive fungal infection in ELBW infants during the first 6 weeks of life.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Early colonization of the skin and mucous membranes with Candida species can progress to candidemia in up to 60% of ELBW infants. [5][6][7] In addition to mortality, neonatal candidemia has been associated with increased NICU lengths of stay and hospital costs. 8 Kaufman et al 7 published the only prospective, randomized, double-blind clinical trial to date that demonstrates effectiveness and safety of fluconazole administration in preventing fungal colonization and invasive fungal infection in ELBW infants during the first 6 weeks of life.…”
Section: Introductionmentioning
confidence: 99%
“…Baley et al (2) observed that 26.7% of low birth weight newborns were colonized by Candida and 7.7% developed invasive disease. Low hemoculture positivity for fungi is an important obstacle to fungemia diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…El porcentaje de RNpret extremos colonizados que presentan una CI varía entre 7 y 28% en diferentes series 16,17 . Manzoni y cols., comunicaron una tasa de progresión a CI de 27,5%, en los pacientes colonizados por Candida spp en tres o más sitios versus 7,2% en aquellos RNpret extremos no colonizados (p < 0,001).…”
Section: Infectología Al Díaunclassified